2016
DOI: 10.1016/j.ijid.2016.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Communicable diseases as health risks at mass gatherings other than Hajj: what is the evidence?

Abstract: Mass gatherings are characterized by the concentration of people temporally and spatially, and may lead to the emergence of infectious diseases due to enhanced transmission between attendees. This is well-demonstrated in the context of the Hajj and Umrah pilgrimages in Saudi Arabia. The goal of this review was to present the available evidence on outbreaks associated with a variety of pathogens, or also the lack thereof, as assessed by thorough surveillance at any mass gatherings with the exception of those in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
79
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 62 publications
1
79
0
1
Order By: Relevance
“…Music and arts festivals present the ideal environment for the transmission of infections like measles, given the large crowds and close prolonged interpersonal contact between individuals [5,6]. The popularity of these events [7] enhances the potential for outbreaks in this type of setting, and it is therefore important to advise festival goers, as well as individuals working or performing at such events, to be fully vaccinated.…”
Section: Discussionmentioning
confidence: 99%
“…Music and arts festivals present the ideal environment for the transmission of infections like measles, given the large crowds and close prolonged interpersonal contact between individuals [5,6]. The popularity of these events [7] enhances the potential for outbreaks in this type of setting, and it is therefore important to advise festival goers, as well as individuals working or performing at such events, to be fully vaccinated.…”
Section: Discussionmentioning
confidence: 99%
“…This fact further illustrates the importance of efforts on water and food health of the participants. [58] In addition, it was observed that the outbreak of waterborne disease with various pathogens (parasites, bacteria, and viruses) occurred due to the lack of personal and public hygiene and insufficient vaccination coverage. [58] Further, in addition to water sanitation, similar supervision should be considered for ice sources as well.…”
Section: Discussionmentioning
confidence: 99%
“…[58] In addition, it was observed that the outbreak of waterborne disease with various pathogens (parasites, bacteria, and viruses) occurred due to the lack of personal and public hygiene and insufficient vaccination coverage. [58] Further, in addition to water sanitation, similar supervision should be considered for ice sources as well. [56] Due to the provision of safe drinking water during the Hajj, the risk of waterborne diseases is low.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations